2020
DOI: 10.1107/s1600577520011170
|View full text |Cite
|
Sign up to set email alerts
|

Bent crystal Laue analyser combined with total reflection fluorescence X-ray absorption fine structure (BCLA + TRF-XAFS) and its application to surface studies

Abstract: A bent crystal Laue analyser (BCLA) is an X-ray energy analyser used for fluorescence X-ray absorption fine-structure (XAFS) spectroscopy to separate the fluorescence X-ray emission line of a target atom from the elastic scattering X-rays and other fluorescence emission lines. Here, the feasibility of the BCLA for total reflection fluorescence XAFS (TRF-XAFS), which has a long X-ray footprint on the substrate surface owing to grazing incidence, was tested. The focal line of the BCLA was adjusted on the X-ray f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…The L 3 edge is superior to the K-edge because of the availability of stronger X-ray sources emitted from the undulator and the high energy resolution; however, the Pt and Au L 3 edges overlap because of their close proximity. In our previous work, , we demonstrated that the BCLA can completely separate the Au L α and Pt L α fluorescence X-rays, enabling an analysis of the Pt XAFS in the k -range beyond 10 Å –1 . Note that the Au effect was not observed because the amount of Au was so small that its incident X-ray absorption and the inelastic scattering of Au fluorescence X-ray were negligible.…”
Section: Results and Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The L 3 edge is superior to the K-edge because of the availability of stronger X-ray sources emitted from the undulator and the high energy resolution; however, the Pt and Au L 3 edges overlap because of their close proximity. In our previous work, , we demonstrated that the BCLA can completely separate the Au L α and Pt L α fluorescence X-rays, enabling an analysis of the Pt XAFS in the k -range beyond 10 Å –1 . Note that the Au effect was not observed because the amount of Au was so small that its incident X-ray absorption and the inelastic scattering of Au fluorescence X-ray were negligible.…”
Section: Results and Discussionmentioning
confidence: 96%
“…(4) The interference of the L 3 edges of Pt and Au can be eliminated by separating the Au and Pt fluorescence Xrays. 46 In the high-energy-resolution fluorescence detection (HERFD)-empowered back-illuminated X-ray absorption near-edge structure (HERFD + BI-XANES) method, another type of crystal monochromator is adopted to reduce the lifetime broadening effect and obtain high-energy-resolution XANES spectra that provide more precise information about the electronic state. HERFD + BI-XANES spectra can be obtained by replacing the BCLA with a Johann-type crystal analyzer.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Herein, we report the high energy resolution fluorescence detection (HERFD) , of the Pt L 3 - and L 2 -edge XANES of a series of Pt-M (M = Ni, Cu) bimetallic samples by carefully selecting Pt L α fluorescence X-rays (L α1 = 9442.3 eV) with a spherically bent crystal analyzer (SBCA) in a Rowland Circle, and we used it to record the HERFD–XANES. It should be noted that HERFD–XANES can also be obtained using similar analyzers such as the bent crystal Laue analyzer (BCLA, smaller size, lower energy resolution) and cylindrically bent crystal analyzer (von Hamos-type, higher efficiency at the expense of sensitivity). …”
Section: Introductionmentioning
confidence: 99%